Hepatitis B virus genotyping, detection of reverse transcriptase resistance and immune escape mutations in persons with chronic hepatitis B from Croatia - Grgić, Ivana, biologinja (Array, 2020)
Approximately 257 million people worldwide live with chronic hepatitis B virus (HBV) infection, which, if left untreated, can lead to liver cirrhosis or hepatocellular carcinoma. The hepatitis B virus is a DNA virus with a reverse transcriptase that has no exonuclease activity, which results in a high mutation rate. Reverse transcriptase inhibitors, which interfere with viral replication, are used to treat the infection. Mutations in the A-B reverse transcriptase interdomain can be associated with resistance to antiviral drugs, as well as immune escape. The aim of this study was to analyze HBV genotypes circulating in the Croatian population and analyze resistance as well as immune escape mutations. A selected A-B reverse transcriptase interdomain was sequenced using the Sanger method. HBV genotypes, subtypes, drug resistance as well as immune escape mutations were analyzed using the Geno2Pheno algorithm in 30 patients with chronic hepatitis B. Genotype A (subtype A2) was detected in 20% and genotype D (subtypes D1, D2 and D3) in 80% of viral isolates. Drug resistance mutations rtL180M and rtM204V were detected only in genotype A isolates. Immune escape mutations R122K and sT131N were detected in all genotype A isolates, while mutations sD144E, sM133I, sM133L, sP120S, sQ101H and sR122K were detected in 8 genotype D isolates. Genotype distribution and the prevalence of mutations observed in this study are in accordance with data from the majority of other European countries.